2017
DOI: 10.1101/122069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-time observation of flexible domain movements in Cas9

Abstract: 20The CRISPR-associated protein Cas9 is a widely used genome editing tool that

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…While we were submitting our manuscript, two similar studies were deposited onto bioRxiv (Dagdas et al, 2017;Osuka et al, 2017). Using smFRET approach to capture dynamic motions of the HNH domain, both studies revealed that Cas9 exhibits three major conformational states, which is consistent with the open, intermediate, and closed Cas9 states we discovered.…”
Section: Dynamic Actions Of Cas9supporting
confidence: 58%
“…While we were submitting our manuscript, two similar studies were deposited onto bioRxiv (Dagdas et al, 2017;Osuka et al, 2017). Using smFRET approach to capture dynamic motions of the HNH domain, both studies revealed that Cas9 exhibits three major conformational states, which is consistent with the open, intermediate, and closed Cas9 states we discovered.…”
Section: Dynamic Actions Of Cas9supporting
confidence: 58%
“…Specifically, smFRET has shown reciprocal changes in the conformational states assumed by HNH and REC2 across multiple DNA substrates, indicating that the conformational dynamics of HNH and REC2 is tightly coupled to ensure catalysis. Notably, the HNH domain has high conformational plasticity, as shown by biochemical and biophysical experiments (Osuka et al ., 2018; Sternberg et al ., 2015) and previous shorter MD simulations (Palermo et al ., 2016). Additionally, in the cryo-EM structure EMD-3277, the HNH and REC2 are observed at a lower resolution (8–10 Å) than the overall structure (6 Å), highlighting their mobility (Jiang et al ., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…used bulk FRET to reveal that the conformational dynamics of the HNH domain controls DNA cleavage (Sternberg et al ., 2015). Subsequently, single-molecule FRET (smFRET) experiments characterized the conformational features of the activated HNH docked at the cleavage site (Dagdas et al ., 2017), and also revealed that the high flexibility of the REC lobe facilitates the activation of the HNH domain (Chen et al ., 2017; Osuka et al ., 2018). Moreover, computational studies have contributed in understanding the conformational dynamics of HNH from the apo form of Cas9 up to the DNA-bound state (Huai et al ., 2017; Palermo et al ., 2017 a , 2017 b ; Zuo and Liu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, low brightness of the luminescent probes has limited the application of luminescent imaging. Recently, several bright and multicolor Osuka et al 2018) smFRET measurements have revealed that HNH nuclease domain of Cas9 assumes two different phases: (a) a static phase in which the HNH domain remains stationary for an extended period (over 100 s) and (b) a fluctuating phase in which the domain moves frequently between multiple positions (Osuka et al 2018). Only during the fluctuating phase, the Cas9 takes structure capable to cleave DNA strands.…”
Section: Advances In Smfret Methodsmentioning
confidence: 99%
“…Thus, the ternary complex has been predicted to take additional temporal conformations beyond the solved crystal structures during DNA cleavage. Single-molecule measurements of intramolecular FRET between probes in the HNH domain and the domain proximal to the DNA cleavage site demonstrated that the ternary complex shows both static and fluctuating phases (Osuka et al 2018). In the static phase, the HNH domain stays at the DNA-undocked position, which is 3-nm away from the DNA cleavage site, for an extended period.…”
Section: Molecular Dynamics Of Proteins Measured By Smfretmentioning
confidence: 99%